Irony, self-mockery, and ironic turns of events. Marian Załucki’s satirical performances - Smyczek, Katarzyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The article offers an analysis of the works of Marian Załucki (a Polish comedian, poet, children’s literature writer, and author of books: Przejażdżki wierszem, U szczypnij muzo, Ojczyste kpiny!, A n ie m ówiłem?, Niespokojna czaszka, Przepraszam żartowałem, Czy lubi pani Załuckiego?), and constitutes an attempt at presenting the specificity of the comedy scene in the PRL.